Acute hemorrhagic cholecystitis as a rare cause of hemobilia - Bockova, M; Pazdírek, F; Šťovíček, J; Stolz, A (Rozhledy v chirurgii, 2023)
Hemobilia is an unusual type of gastrointestinal bleeding most frequently due to iatrogenic injury, trauma, or neoplasia. Acute cholecystitis as a cause of hemobilia is rare. We present the case study of a patient with bleeding from eroded gallbladder mucosa in the setting of severe calculous cholecystitis. The hemorrhagic episode was preceded by acute ERCP due to obstructive icterus with extraction of the calculi, followed by the development of severe acute pancreatitis. These factors initially misled the diagnosis. The bleeding was not hemodynamically important and routine diagnostic methods did not reveal its exact source. Direct choledochoscopy (SpyGlassTM) proved to be helpful in determining the right diagnosis, as it ruled out any injury or tumor in the main bile ducts and considerably supported the assumption of intrabladder bleeding. Surgical revision confirmed the cause, and subsequent cholecystectomy solved the whole problem.
Keywords: cholecystitida; cholangioscopy; pankreatitida; Humans; hemobilie; lidé; cholangiocarcinoma; akutní cholecystitida; Cholecystitis; choledochoscopy; hemorrhagic cholecystitis; gastrointestinální krvácení; Gastrointestinal Hemorrhage; Hemobilia; endoscopic intervention; Cholecystitis, Acute; Pancreatitis; hemobilia; Acute Disease; akutní nemoc